1996
DOI: 10.1021/jp953703p
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intersystem Crossing in the Dynamics of the O(3P) + C2H5I Reaction

Abstract: Reactive scattering of O( 3 P) atoms with C 2 H 5 I molecules has been studied at initial translational energies E ∼ 51 and 16 kJ mol -1 using a supersonic beam of O atoms seeded in He and Ne buffer gas generated from a microwave discharge source. A mildly forward-and backward-peaked angular distribution of IO product observed at lower initial translational energy becomes backward-scattered at higher initial translational energy. An isotropic angular distribution is observed for HOI product at lower initial tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 20 publications
3
35
0
Order By: Relevance
“…Neither is obviously flawed, although the authors of the discharge-fast flow study 3 (smaller k 1 value) suggested that the laser photolysis-resonance fluorescence study 2 (larger k 1 value) may have been affected by unrecognized secondary chemistry that consumed OH, even though the latter authors sought such effects by variation of the laser intensity but did not observe systematic changes in k 1 . The present data yield the first Arrhenius parameters for reaction 1, and the A factor found here, around 10 -11 cm 3 molecule -1 s -1 , implies a fairly loose TS and is typical of A factors found for H abstraction reactions by OH from, for example, H 2 or CH 4 . 25 The rate constant at the mean tropospheric temperature of 277 K, estimated from eq 4 to be 4.0 × 10 -14 cm 3 molecule -1 s -1 , is about 5 times that for OH + CH 3 CCl 3 , and thus the tropospheric lifetime of CF 3 I with respect to OH attack is about 0.2 of that of CH 3 CCl 3 , i.e., about 1.5 years.…”
Section: E[g2(mp2)] ) E[qcisd(t)/6-311g(dp)]supporting
confidence: 78%
“…Neither is obviously flawed, although the authors of the discharge-fast flow study 3 (smaller k 1 value) suggested that the laser photolysis-resonance fluorescence study 2 (larger k 1 value) may have been affected by unrecognized secondary chemistry that consumed OH, even though the latter authors sought such effects by variation of the laser intensity but did not observe systematic changes in k 1 . The present data yield the first Arrhenius parameters for reaction 1, and the A factor found here, around 10 -11 cm 3 molecule -1 s -1 , implies a fairly loose TS and is typical of A factors found for H abstraction reactions by OH from, for example, H 2 or CH 4 . 25 The rate constant at the mean tropospheric temperature of 277 K, estimated from eq 4 to be 4.0 × 10 -14 cm 3 molecule -1 s -1 , is about 5 times that for OH + CH 3 CCl 3 , and thus the tropospheric lifetime of CF 3 I with respect to OH attack is about 0.2 of that of CH 3 CCl 3 , i.e., about 1.5 years.…”
Section: E[g2(mp2)] ) E[qcisd(t)/6-311g(dp)]supporting
confidence: 78%
“…[60][61][62] At low initial translational energy, 3.8 kcal mol Ϫ1 , both IO and HOI products from the O͑ 3 P͒ϩC 2 H 5 I reaction emerge from the OIC 2 H 5 complex, as has been shown in crossed molecular beam experiments. 61͑a͒ The formation of the HOI product arises from the OIC 2 H 5 complex through a five-centered ring transition state in which the H atom migrates to the oxygen from the terminal CH 3 group.…”
Section: Vibrational Energy Disposal and Comparison With X؉hbr Himentioning
confidence: 61%
“…31 In the gas phase, IVR is observed in polyatomic molecules at energies where vibrational state densities exceed ϳ10-100 states/cm Ϫ1 . 37 The lifetime of the Br II complex ͑bound by ϳ60 kJ/mol) was ϳ44 ps at a center-ofmass collision energy of 1.7 kJ/mol, dropping to ϳ5 ps and 3 ps for collision energies of 52 kJ/mol and 87 kJ/mol, respectively. Vibrational state densities for these transient ''physisorbed complexes'' consisting of an incident molecule interacting with several surface atoms ͑oscillators͒ are greater than 10 5 states/cm Ϫ1 even at the threshold energy for dissociative chemisorption.…”
Section: A Applicability Of a Statistical Treatment Of Gas-surface Rmentioning
confidence: 96%